(untitled) (Medico Legal Update, 2020)
Background: Ventilator-Associated Pneumonia (VAP) is one of the popular Intensive Care Units (ICUs) nosocomial infections with a prevalence rate of ten to seventy percent. The frequency of VAP is about twenty percent. Lack of awareness of VAP standards and the low quality of nursing practice can become a barrier to preventing VAP. Objective: The purpose of this study is to assess the knowledge of nurses concerning VAP prevention in Mosul teaching Hospitals. Material and Method: A descriptive design study was used to assess knowledge and sources of knowledge among nurses about VAP prevention. From Mosul Teaching Hospitals picked 200 respondents working in different intensive care areas (ICU, CCU, NICU, and PICU) as a sample for the current study using the accidental sampling approach. Aquestionnaire developed for nurses have been updated and revised for the purpose of the study. The questionnaire was tested for validity and reliability and passed for use in the present study. Using Microsoft Excel, data coding, entry, cleaning, and analysis were done, and results were presented using standard frequency distribution tables. Results: In relation to Sociodemographic data of the studied sample is shown in Table 1. The average age of nurses was founded (26.13 ± 4.25) years, and (62.7 %) had a diploma in nursing (secondary schools). Also, the mean experience period was (7.31 ± 3.81) years. The study found that (67%) of Nurses had poor knowledge about pneumonia and VAP. The highest (86%) of nurse’s little knowledge was gained through their practice of nursing in Mosul hospital. Conclusion: Multieducational and training courses and programs need for nurses to improve their knowledge about prevention of VAP and may decrease Pneumonia associated with Ventilator among patients were concluded in current study.